Answer:
x = 10
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Step-by-step explanation:
<u>Step 1: Define</u>
6(x - 1) = 9(x - 4)
<u>Step 2: Solve for </u><em><u>x</u></em>
- Distribute: 6x - 6 = 9x - 36
- Subtract 6x on both sides: -6 = 3x - 36
- Isolate <em>x</em> term: 30 = 3x
- Isolate <em>x</em>: 10 = x
- Rewrite: x = 10
<u>Step 3: Check</u>
<em>Plug in x into the original equation to verify it's a solution.</em>
- Substitute in <em>x</em>: 6(10 - 1) = 9(10 - 4)
- Subtract: 6(9) = 9(6)
Here we see that the 2 expressions are exactly the same.
∴ x = 10 is the solution to the equation.
Answer:
Well around 5-8 miles were jogged daily.
Step-by-step explanation:
Thats all i know
The slope would be 0
This is basically how you do it if you need more help let me know
4x - 2x + 8 = 6(x + 4) Given
(4x - 2x) + 8 = 6(x + 4)
2x + 8 = 6(x + 4) Combine like terms
2x + 8 = (6)(x) + (6)(4)
2x + 8 = 6x + 24 Distributive Property
2x - 6x + 8 = 6x - 6x + 24
-4x + 8 = 24 Subtraction Property of Equality
-4x + 8 - 8 = 24 - 8
-4x = 16 Subtraction Property of Equality
-4x : (-4) = 16 : (-4)
x = -4 Division Property of Equality
The numerical coefficient in y= -6x-3 is -6